Outcomes of Platinum-Sensitive Small-Cell Lung Cancer Patients Treated With Platinum/Etoposide Rechallenge: A Multi-Institutional Retrospective Analysis - (:unkn) unknown (CIG MEDIA GROUP, LP, 2015)
Small-cell lung cancer has a high chemotherapeutic sensitivity but with disappointing outcome results. Patients with sensitive disease are those who respond to treatment with a long relapse-free interval (RFI): in these cases rechallenge with first-line chemotherapy might represent a therapeutic opportunity. Our largest retrospective experience confirmed that rechallenge is feasible with interesting outcome results; there are no statistical differences between RFI and outcome. Introduction: Patients with small-cell lung cancer (SCLC) that progresses after first-line (FL) chemotherapy have a poor prognosis and second-line (SL) chemotherapy has limited efficacy. Patients whose disease relapses/progresses > 90 days after FL platinum-based treatment are considered platinum-sensitive and could be rechallenged with a similar regimen. We conducted a multicenter retrospective analysis to evaluate outcomes of SCLC patients rechallenged with platinum/etoposide. Patients and Methods: Records of all SCLC patients treated in 7 institutions between January 2007 and December 2011 were reviewed. The primary end point was overall survival from the time of rechallenge (OS-R); secondary end points were progression-free survival (PFS) and overall survival from the time of diagnosis (OS-D). Survival curves were calculated using the Kaplan-Meier method. Results: Of the 2000 SCLC patients identified, 112 (5.6%) had sensitive disease treated with rechallenge platinum/etoposide; 65% were men with a median age of 64 years. At the time of diagnosis, 44% of patients had limited disease, 82% had an Eastern Cooperative Oncology Group performance status of 0 to 1. A median of 4 cycles of rechallenge was administered. Tumor response was 3% for complete response and 42% for partial response, 19% of patients maintained stable disease, 27% progressive disease, and 9% were not evaluable. Median PFS from the time of rechallenge was 5.5 months (95% confidence interval [CI], 4.4-6.3). Median OS-R and OS-D were 7.9 months (95% CI, 6.9-9.7) and 21.4 months (95% CI, 19.8-24.1), respectively. Subgroup analysis according to relapse-free interval (90-119 vs. 120-149 vs. > 150 days) did not show any statistically significant difference in PFS or OS-R. Conclusion: The outcome for SL chemotherapy for SCLC is poor. Rechallenge platinum/etoposide is a reasonable option with potentially better outcomes than standard chemotherapy.
Keywords: Extended disease; Platinum sensitive; Rechallenge chemotherapy; SCLC; Second-line; 2ND-LINE TREATMENT; PHASE-III; CHEMOTHERAPY; TOPOTECAN; GUIDELINES; THERAPY; RELAPSE